A Pyroptosis-Related Gene Signature for Predicting Survival in Glioblastoma - Li, Xin-Yu; Zhang, Lu-Yu; Li, Xue-Yuan; Yang, Xi-Tao; Su, Li-Xin (Frontiers in Oncology, 2021)
Background: In this study, a prognostic model based on pyroptosis-related genes was established to predict overall survival (OS) in patients with Glioblastoma (GBM). Methods: The gene expression data and clinical information of GBM patients were obtained from The Cancer Genome Atlas (TCGA), and bioinformatics analysis of differentially expressed genes was performed. LASSO Cox regression model was used to construct a three-pyroptosis-related gene signature, and validation performed using an experimental cohort. Results: A total of 3 pyroptosis-related genes (CASP4, CASP9, and NOD2) were used to construct a survival prognostic model, and experimental validation performed using an experimental cohort. Receiver operating characteristic (ROC) analysis was performed and the area under the ROC curves (AUC) was 0.921, 0.840, and 0.905 at 1, 3, and 5 years, respectively. Functional analysis revealed that T cell activation, regulation of T cell activation, leukocyte cell-cell adhesion, positive regulation of cell adhesion among other immune-related functions were enriched, and immune-related processes were different between the two risk groups. Conclusion: In this study, a novel prognostic model based on three pyroptosis-related genes is constructed and used to predict the prognosis of GBM patients. The model can accurately and conveniently predict the 1- 3-and 5-year OS of GBM patients.